Perkembangan Model Mental Mahasiswa pada Penggunaan Bahan Ajar Kesetimbangan Kimia berbasis Inkuiri Terbimbing - Faizah Qurrata Aini; Zonalia Fitriza; Fauzana Gazali; Mawardi Mawardi; Ghery Priscylio (JURNAL EKSAKTA PENDIDIKAN (JEP), 2019)
This research aimed to analyze students' mental models in chemical equilibrium before and after using guided inquiry-based learning material. The instrument used was a conceptual test which has been developed by Bergquist and Heikkinen. This test was taken before and after formal instruction using the learning material. Responses were obtained from 30 first-year students of Faculty of Mathematics and Natural Science of UNP which taking general chemistry course in 2017/2018 even semester using purposive sampling. Student answers to this test were analyzed descriptively. From this research, student understanding increase after using the learning material. The highest increasing is in equilibrium shifting stoichiometry concept. This gaining correlated to students’ mental model development. The results of this study indicated that in general there has been a development of students’' mental models before and after using this learning material. Although, not all students’ model mental are appropriate to scientific concepts in chemical equilibrium.